The Analysis of the Implementation of Qur'an Reading-Writing Method in Improving the Qur'an Reading Quality at MTS Al-Washliyah Pancur Batu - Astari, Ririn Tri; Zailani, Zailani (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2023)
The problem in this study was the quality of students reading Qur'an which were relatively low. This research was conducted qualitative to analyse the implementation of the reading-writing method to improve the Qur'an reading quality of students. The method used in this research was descriptive qualitative which sought the truth of an object carried out in scientific conditions. Data collection techniques used were observation, interviews and documentation. The stages of data analysis in this research were data reduction, data presentation, and data verification. The results of this study consisted of four stages: planning, implementation, and evaluation of the Qur'anic Writing and Reading Program. From the results of the study, it can be concluded that the Analysis of Reading-Writing Qur'an at MTs Al-Washliyah Pancur Batu is quite good. In relation to the Reading-Writing Method for students as well as the role of school principals and teachers of Writing and Reading Al-Quran can make a major contribution in order to improve student achievement in terms of reading the Qur'an with tartil and with recitations and quality of their reading of the Qur'an according to the rules of Tajweed.